Enrichment Programme Efficacy on Core Life Skills: A Quasi Experimental Study Among University Students - Joshi, Neha; Sharma, Seema; Sharma , Preeti (Indian Journal of Extension Education, 2022)
The present study was conducted in 2021, with an objective to examine the impact of enrichment programme on core life skills of undergraduate students. The study consisted of 60 first year undergraduates of Punjab Agricultural University enrolled in 2021-2022 academic session havinglow level of overall life skill. Life Skills Assessment Scale by Nair et al., (2010) was used to collect the data on measuring variable. One group quasi experimental research design was conducted by using module based online training sessions for the intervention. Evaluation of pre-intervention data highlighted that all the student participants were in low level life skill with none at average and high levels, whereas, in post-intervention evaluation, more students were found at average and high levels with merely few of them remained in low level of life skill. Dimension-wise analysis indicated significantly improved in each dimensions of life skills with non-significant gender differences after attending enrichment programme. The study recommends that life skills education should be an integral part of the university curriculum mainly at graduation level for optimal development of required psychosocial skills among 21st century youngsters enabling them to lead a successful living.
Keywords: Core life skills; Undergraduate students; Gender; Enrichment programme; Efficacy assessment